A lithium-ion battery and a method for predicting and regulating the membrane resistance of a lithium-ion battery

By using conductive agents and binders with specific functional groups in the negative electrode coating material of lithium-ion batteries, and using mathematical models to optimize the material proportion and compaction density, the problem of large resistance of the negative electrode sheet diaphragm is solved, and the rate performance and battery design efficiency of the lithium-ion battery are improved.

CN119627034BActive Publication Date: 2025-04-29JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510151887.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-29
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

The existing solutions to improve the conductivity of silicon-based negative electrode materials can easily lead to a large diaphragm resistance of the negative electrode sheet, resulting in a reduction in the overall performance of lithium-ion batteries.

Method used

The diaphragm resistance of the negative electrode sheet is predicted and regulated by selecting a second conductive agent containing hydroxyl (-OH) and carboxyl (-COOH) functional groups and a second binder containing carboxyl functional groups in the negative electrode coating material, and optimizing the second conductive agent ratio, the second binder ratio and the compaction density of the negative electrode sheet through mathematical model.

Benefits of technology

Effectively optimize the diaphragm resistance of the negative electrode sheet, improve the rate performance of lithium-ion batteries, and improve the efficiency of battery design.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a lithium-ion battery and a method for predicting and regulating the membrane resistance of a lithium-ion battery. The lithium-ion battery comprises a battery core; the battery core comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the positive electrode sheet comprises a positive electrode current collector and a positive electrode coating material coated thereon; the negative electrode sheet comprises a negative electrode current collector and a negative electrode coating material coated thereon; the positive electrode coating material comprises a positive electrode active material, a first conductive agent and a first binder; the negative electrode coating material comprises a negative electrode active material, a second conductive agent and a second binder; the average membrane resistance R of the negative electrode sheet β Satisfies the following relationship: 0.9≤R β / |(e (1‑(a / (a+b)) ‑0.8×c) / 100|≤1.1; a represents the mass percentage of the second conductive agent in the negative electrode coating material; b represents the mass percentage of the second binder in the negative electrode coating material; c represents the compaction density of the negative electrode sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium ion battery and a method for predicting and regulating the membrane resistance of a lithium ion battery. Background Art

[0002] Silicon-based negative electrode materials have become an ideal choice for current high-energy-density lithium-ion battery applications due to their ultra-high theoretical gram capacity, low lithium desorption potential, and abundant resource reserves. These advantages make silicon-based negative electrode materials show great potential in battery technology, especially when paired with high-nickel (nickel cobalt manganese oxide / nickel cobalt aluminum oxide) positive electrode materials, they can achieve better overall performance.

[0003] However, one of the main problems facing silicon-based negative electrode materials is their poor electrical conductivity, which will seriously affect the rate charge and discharge performance of lithium-ion batteries. To address this problem, the current commonly used solution is to introduce a conductive agent into the material and use a simple physical mixing method with a polymer binder (such as SBR) to improve the conductivity of silicon-based negative electrode materials. However, this simple method of adding a conductive agent and a polymer binder will, on the one hand, lead to uneven dispersion of the conductive agent, which is prone to the problem of conductive agent agglomeration and cannot effectively improve the conductivity of the negative electrode sheet; on the other hand, it does not take into account the influence of the added conductive agent and bonding on the membrane resistance of the negative electrode sheet, which is likely to lead to a large membrane resistance of the negative electrode sheet. The membrane resistance and the rate of lithium-ion batteries have a strong correlation, which is not conducive to the improvement of the overall performance of lithium-ion batteries. Summary of the invention

[0004] The purpose of the present invention is to propose a lithium-ion battery with predictable and controllable diaphragm resistance, which solves the problem that the existing solutions for improving the conductivity of silicon-based negative electrode materials easily lead to a large diaphragm resistance of the negative electrode plate, resulting in a decrease in the overall performance of the lithium-ion battery.

[0005] To achieve the above object, the present invention is implemented by the following technical solutions:

[0006] The present invention provides a lithium-ion battery, which includes a battery core; the battery core is composed of a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, the positive electrode sheet is composed of a positive electrode current collector and a positive electrode coating material coated on at least one surface thereof, the negative electrode sheet is composed of a negative electrode current collector and a negative electrode coating material coated on at least one surface thereof, the positive electrode coating material includes a positive electrode active material, a first conductive agent and a first binder, the negative electrode coating material includes a negative electrode active material, a second conductive agent and a second binder, and the second conductive agent is selected from a material containing a hydroxyl (-OH) and a carboxyl (-COOH) functional group, and the second binder is selected from a material containing a carboxyl functional group,

[0007] Among them, the average film resistance R of the negative electrode sheet β Satisfies the following relationship:

[0008] 0.9≤R β / |(e (1-(a / (a+b)) -0.8×c) / 100|≤1.1; where: R β Represents the average film resistance of the negative electrode sheet, its unit is Ω·cm 2 ; a represents the mass percentage of the second conductive agent in the negative electrode coating material; b represents the mass percentage of the second binder in the negative electrode coating material; c represents the compaction density of the negative electrode sheet, and its unit is g / cm 3 .

[0009] Specifically, the positive electrode current collector includes a coated area and an uncoated area of ​​the positive electrode coating material, and the uncoated area of ​​the positive electrode coating material accounts for 1 to 10% of the area of ​​the positive electrode current collector; the negative electrode current collector includes a coated area and an uncoated area of ​​the negative electrode coating material, and the uncoated area of ​​the negative electrode coating material accounts for 2 to 11% of the area of ​​the negative electrode current collector.

[0010] Furthermore, a lithium-ion battery: also satisfies the following conditions 2×10 -3 ≤|(e (1-(a / (a+b)) -0.8×c) / 100|≤1.5×10 -2 .

[0011] Specifically, the present invention provides a lithium-ion battery, wherein a new mathematical model R for predicting and regulating membrane resistance is constructed. α (R α =|(e (1-(a / (a+b)) -0.8×c) / 100|), which can be used to describe the relationship between the negative electrode sheet resistance and the mass percentage a of the second conductive agent, the mass percentage b of the second binder and the degree of compaction c. By optimizing these parameters through this mathematical model, it is possible to achieve precise control of the performance of the negative electrode material, which is beneficial to optimize the design of the negative electrode sheet, thereby further improving the overall performance of the lithium-ion battery. The mathematical model can improve the optimization design efficiency of the negative electrode sheet, thereby improving the efficiency of the battery design.

[0012] Furthermore, in a lithium-ion battery, the negative electrode coating material also includes a thickener.

[0013] Furthermore, in a lithium-ion battery, the thickener is sodium carboxymethyl cellulose, and the mass percentage of the thickener in the negative electrode coating material is 0.5-1.5%.

[0014] Furthermore, a lithium-ion battery: the negative electrode active material is selected from at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon carbon, silicon oxygen and pre-lithium silicon oxygen, and the silicon content in the negative electrode active material is 1.0-25.0wt%; the second conductive agent is selected from carbon nanotubes or a combination of carbon nanotubes and carbon black; the second binder is selected from at least one of polyacrylic acid, polyacrylonitrile, and polystyrene-acrylic acid.

[0015] The carboxyl functional groups on the second binder can form dipole interactions or hydrogen bonds with functional groups such as hydroxyl groups on the second conductive agent carbon nanotubes, thereby making the carbon nanotubes more evenly dispersed in the three-dimensional cross-linked network structure of polyacrylic acid, thereby improving the conductivity of the negative electrode sheet.

[0016] Furthermore, in a lithium ion battery, the mass percentage a of the second conductive agent satisfies 0<a≤1.5%, and the mass percentage b of the second binder satisfies 0<b<3.0%; the mass percentage a of the second conductive agent and the mass percentage b of the second binder satisfy 1.0%≤a+b≤3.0%.

[0017] Specifically, the characterization method of the mass percentage of the second binder in the negative electrode coating material is as follows: Taking polyacrylic acid as an example: first, the negative electrode plate that has been rinsed with dimethyl carbonate and vacuum dried is placed in an ethyl acetate solution and ultrasonically treated for 1 hour; then, after centrifugation and filtration, gas chromatography-mass spectrometry (GC-MS) is used to qualitatively analyze the polyacrylic acid in the negative electrode plate; if the presence of polyacrylic acid is detected, thermogravimetric analysis (TG) will be further used to measure the relationship between the change in mass of the negative electrode plate with temperature during heating, so as to determine the mass percentage of polyacrylic acid (it is known that the decomposition temperature of pure polyacrylic acid is 150°C, and a commercial polyacrylic acid standard sample can also be used for TG testing to determine its decomposition temperature range).

[0018] Specifically, the characterization method of the mass percentage of the second conductive agent in the negative electrode coating material is as follows: Taking carbon nanotubes as an example: Under a cold field emission scanning electron microscope (FE-SEM), carbon nanotubes appear in the form of long strips (micrometer-level length and nanometer-level diameter), acetylene black is in the form of nanometer-level spheres, graphite is in the form of micrometer-level lamellar layers, and silicon and silicon carbon are micrometer-level granular materials. In order to further indirectly characterize the content of carbon nanotubes in the negative electrode coating material, carbon nanotubes (0-5%) of different mass ratios are mixed with the negative electrode active material, and a positive correlation function is established based on the ratio of the area occupied by the carbon nanotubes in the cross-section diagram to the cross-section area of ​​the entire negative electrode coating material, combined with the mass fraction of the added carbon nanotubes, to determine the mass percentage of the carbon nanotubes in the negative electrode coating.

[0019] Furthermore, a lithium-ion battery: the compaction density c of the negative electrode sheet satisfies 1.2 g / cm3 ≤c≤1.8g / cm 3 .

[0020] Furthermore, in a lithium-ion battery, the capacity N / P ratio of the negative electrode plate to the positive electrode plate is (1.02-1.1):1.

[0021] Furthermore, a lithium-ion battery: the molecular formula of the positive electrode active material is expressed as: Li a Ni x Co y Mn z M b O2; wherein, 0.9<a<1.2, 0.8≤x≤0.93, 0.1≤y<0.4, 0.05≤z<0.4, 0≤b≤0.1, and M represents at least one element selected from Zr, W, Ti, Al, Sr, La, B, and Nd.

[0022] Furthermore, in a lithium-ion battery: the first conductive agent is conductive carbon black and / or carbon nanotubes, and the proportion of the first conductive agent in the positive electrode coating material is 1.0 to 3.0 wt%; the first binder is polyvinylidene fluoride, and the proportion of the first binder in the positive electrode coating material is 1.0 to 3.0 wt%.

[0023] Further, a lithium-ion battery: the electrolyte includes a lithium salt, a solvent and an additive; the lithium salt is selected from any one or more combinations of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide; the solvent is selected from any one or more combinations of dimethyl carbonate, diethyl carbonate, ethylene carbonate, and ethyl methyl carbonate; the additive is selected from any one or more combinations of propylene carbonate, butylene carbonate, ethyl acetate, ethyl methyl carbonate, vinylene carbonate, and fluoroethylene carbonate. Preferably, the electrolyte additive helps to reduce the battery membrane resistance and improve the electrochemical performance of the lithium-ion battery.

[0024] The present invention also provides an electrical device, which comprises the above-mentioned lithium-ion battery.

[0025] The present invention also provides a method for predicting and regulating the membrane resistance of a lithium-ion battery, the method comprising: according to the average membrane resistance R of the negative electrode sheet β Satisfied relationship: 0.9≤R β / |(e (1-(a / (a+b)) -0.8×c) / 100|≤1.1, according to 2×10 -3 ≤|(e (1-(a / (a+b)) -0.8×c) / 100|≤1.5×10 -2The relationship is used to predict and control the membrane resistance of the lithium-ion battery by adjusting the mass percentage a of the second conductive agent in the negative electrode coating material, the mass percentage b of the second binder in the negative electrode coating material, and the compaction density c of the negative electrode sheet.

[0026] Beneficial effects of the present invention:

[0027] (1) The lithium-ion battery proposed in the present invention constructs a mathematical formula, according to which the three variables of the second conductive agent ratio, the second binder ratio and the compaction density can be adjusted to effectively optimize the membrane resistance of the negative electrode sheet, thereby improving the efficiency of the battery design. That is, the mathematical formula constructed by the present invention can be used to calculate the membrane resistance of the negative electrode sheet in the lithium-ion battery by adjusting the mixing ratio of the second conductive agent and the second binder and the compaction density of the negative electrode sheet, and the membrane resistance has a strong correlation with the rate of the lithium-ion battery, which is conducive to optimizing the design of the negative electrode sheet, reducing the resistance, and thus improving the rate performance of the battery.

[0028] (2) The present invention can predict the membrane resistance of the negative electrode sheet by adjusting the ratio of the second conductive agent to the second binder and the compaction density, and can adjust the membrane resistance by adjusting the three parameters. The mathematical formula constructed by the present invention is effective for the average membrane resistance R of the negative electrode sheet obtained by actual testing. β The model of the negative electrode sheet estimates the membrane resistance R α The deviation of the results is small, indicating the accuracy of the mathematical formula of the present invention in predicting the results.

[0029] (3) The present invention can evenly disperse the second conductive agent on the second binder by optimizing the second conductive agent and the second binder, and utilize the dipole interaction or hydrogen bonding between the functional groups on the second conductive agent and the second binder, and reduce the film resistance of the negative electrode sheet by utilizing the three-dimensional cross-linked network structure of the second binder. Specifically, the present invention improves the conductivity of the silicon-based negative electrode material by introducing the second binder and the second conductive agent, thereby improving the rate performance of the lithium-ion battery; the second binder can enhance the interaction with the negative electrode active material because it contains -COOH, and with appropriate compaction, it can effectively improve the interfacial bonding force between the active materials and between the active materials and the negative electrode current collector. In addition, the rich -OH and -COOH contained in the second conductive agent can be evenly distributed on the surface of the second binder through dipole interaction or hydrogen bonding, forming a uniformly distributed excellent conductive network, ensuring the rapid migration of electrons and lithium ions during the charge and discharge process. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] This embodiment 1 provides a lithium ion battery, the lithium ion battery comprising a battery roll core;

[0033] The battery coil core is composed of a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet is composed of a positive electrode current collector (aluminum foil) and a positive electrode coating material coated on the surface of the positive electrode current collector. The negative electrode sheet is composed of a negative electrode current collector (copper foil) and a negative electrode coating material coated on both sides of the negative electrode current collector. The positive electrode coating material includes a positive electrode active material, a first conductive agent (conductive carbon black, carbon nanotubes) and a first binder (polyvinylidene fluoride). The negative electrode coating material includes a negative electrode active material (silicon carbon material), a second conductive agent (carbon nanotubes), a second binder (polyacrylic acid) and a thickener (sodium carboxymethyl cellulose).

[0034] Among them, the average film resistance R of the negative electrode sheet β Satisfies the following relationship: 0.9≤R β / |(e (1-(a / (a+b)) -0.8×c) / 100|≤1.1; wherein: a represents the mass percentage of the second conductive agent in the negative electrode coating material; b represents the mass percentage of the second binder in the negative electrode coating material; and c represents the compaction density of the negative electrode sheet.

[0035] The method for manufacturing a lithium-ion battery provided in the above embodiment 1 comprises the following specific steps:

[0036] 1. Production of positive electrode:

[0037] Take the positive electrode active material (Li1Ni 0.9 Co 0.3 Mn 0.1 Al 0.05 O2), conductive carbon black, carbon nanotubes and polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system at a mass ratio of 96:1:1:2 to obtain a positive electrode coating material, and then the positive electrode coating material is evenly coated on a 12.0 μm thick positive electrode collector (aluminum foil), and after drying and cold pressing, a positive electrode sheet is obtained;

[0038] 2. Production of negative electrode sheet:

[0039] The negative electrode sheet includes a negative electrode current collector (copper foil) and a negative electrode coating material coated on both sides of the copper foil. Calculated by mass percentage, the negative electrode coating material includes 96.0% silicon-carbon material (Si content 10.0%, graphite content 86.0%), 1.5% carbon nanotubes, 1.0% thickener sodium carboxymethyl cellulose (CMC) and 1.5% binder polyacrylic acid (PAA). The above substances are added to deionized water and stirred to form a negative electrode coating material with a solid content of 40%. The negative electrode coating material is then evenly coated on both sides of the negative electrode current collector (copper foil), and after drying and cold pressing, a negative electrode sheet is formed with a compaction density of 1.5g / cm 3 ;

[0040] 3. Preparation of electrolyte:

[0041] Lithium hexafluorophosphate and an organic solvent of ethylene carbonate (EC): fluoroethylene carbonate (FEC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) are mixed in a ratio of 15:15:20:50 to obtain an electrolyte, wherein the concentration of lithium hexafluorophosphate in the electrolyte is 1.0 mol / L, and 1.0 wt% of lithium difluorophosphate and 0.15 wt% of vinylene carbonate are added;

[0042] 4. Diaphragm:

[0043] A high-porosity diaphragm is selected, in which the thickness of the base film PE is 9.0 μm, the thickness of the ceramic coating on both sides of the base film is 1.0 μm, and the thickness of the PVDF coating is 1.0 μm. The air permeability of the diaphragm is 80-170 s / 100 mL;

[0044] 5. Assembly of lithium-ion batteries:

[0045] The positive electrode sheet and the negative electrode sheet are rolled and slit respectively, and then wound together with the separator to obtain a 21700 cylindrical battery core, which is then welded to the connecting sheet and loaded into a battery shell. After completing the injection, sealing and formation processes, the lithium-ion battery of Example 1 is obtained. The shell of the lithium-ion battery is a cylinder with the size parameters of diameter: 21.0 mm and length 70.0 mm.

[0046] Example 2

[0047] This embodiment 2 provides a lithium-ion battery. The difference between this embodiment 2 and embodiment 1 is that the mass percentage a of the carbon nanotubes (second conductive agent) added during the preparation of the negative electrode plate is 0.25%, the mass percentage b of the polyacrylic acid (second binder) added is 2.75%, and the other conditions are the same as those in embodiment 1.

[0048] Example 3

[0049] This embodiment 3 provides a lithium-ion battery. The difference between embodiment 3 and embodiment 1 is that the mass percentage a of carbon nanotubes added during the preparation of the negative electrode plate is 0.5%, the mass percentage b of polyacrylic acid added is 2.5%, and the rest is the same as embodiment 1.

[0050] Example 4

[0051] This embodiment 4 provides a lithium-ion battery. The difference between embodiment 4 and embodiment 1 is that the mass percentage a of carbon nanotubes added during the preparation of the negative electrode plate is 0.75%, the mass percentage b of polyacrylic acid added is 0.75%, and the rest is the same as embodiment 1.

[0052] Example 5

[0053] This embodiment 5 provides a lithium-ion battery. The difference between embodiment 5 and embodiment 1 is that the mass percentage a of carbon nanotubes added during the preparation of the negative electrode plate is 1.0%, the mass percentage b of polyacrylic acid added is 2.0%, and the rest is the same as embodiment 1.

[0054] Example 6

[0055] This embodiment 6 provides a lithium-ion battery. The difference between this embodiment 6 and embodiment 1 is that the mass percentage a of carbon nanotubes added during the preparation of the negative electrode plate is 1.25%, the mass percentage b of polyacrylic acid added is 1.75%, and the other conditions are the same as those in embodiment 1.

[0056] Example 7

[0057] This embodiment 7 provides a lithium ion battery. The difference between embodiment 7 and embodiment 1 is that the compaction density of the negative electrode sheet of embodiment 7 is 1.2 g / cm 3 , the other conditions are the same as those in Example 1.

[0058] Example 8

[0059] This embodiment 8 provides a lithium ion battery. The difference between embodiment 8 and embodiment 1 is that the compaction density of the negative electrode sheet of embodiment 8 is 1.25 g / cm 3 , the other conditions are the same as those in Example 1.

[0060] Example 9

[0061] This embodiment 9 provides a lithium ion battery. The difference between embodiment 9 and embodiment 1 is that the compaction density of the negative electrode sheet of embodiment 9 is 1.3 g / cm 3 , the other conditions are the same as those in Example 1.

[0062] Example 10

[0063] This embodiment 10 provides a lithium ion battery. The difference between embodiment 10 and embodiment 1 is that the compaction density of the negative electrode sheet of embodiment 10 is 1.35 g / cm 3 , the other conditions are the same as those in Example 1.

[0064] Embodiment 11

[0065] This embodiment 11 provides a lithium ion battery. The difference between embodiment 11 and embodiment 1 is that the compaction density of the negative electrode sheet of embodiment 11 is 1.4 g / cm 3 , the other conditions are the same as those in Example 1.

[0066] Example 12

[0067] This embodiment 12 provides a lithium ion battery. The difference between embodiment 12 and embodiment 1 is that the compaction density of the negative electrode sheet of embodiment 12 is 1.45 g / cm 3 , the other conditions are the same as those in Example 1.

[0068] Embodiment 13

[0069] This embodiment 13 provides a lithium ion battery. The difference between this embodiment 13 and embodiment 1 is that the compaction density of the negative electrode sheet in embodiment 13 is 1.6 g / cm 3 The second binder in Example 13 is polyacrylonitrile, the silicon content in the negative electrode active material in Example 13 is 5.0wt%, and the molecular formula of the positive electrode active material in Example 13 is Li 0.95 Ni 0.8 Co 0.1 Mn 0.05 O2, the first conductive agent in Example 13 accounts for 1.0wt% of the positive electrode coating material, and the first binder in Example 13 accounts for 1.0wt% of the positive electrode coating material.

[0070] Embodiment 14

[0071] This embodiment 14 provides a lithium ion battery. The difference between embodiment 14 and embodiment 1 is that the compaction density of the negative electrode sheet in embodiment 14 is 1.55 g / cm 3 The second binder in Example 14 is polystyrene-acrylic acid, the silicon content in the negative electrode active material in Example 14 is 23.0wt%, and the molecular formula of the positive electrode active material in Example 14 is Li 1.1 Ni 0.92 Co 0.35 Mn 0.3 Zr 0.1O2, the first conductive agent in Example 14 accounts for 3.0wt% of the positive electrode coating material, and the first binder in Example 14 accounts for 3.0wt% of the positive electrode coating material.

[0072] Comparative Example 1

[0073] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, no carbon nanotubes are added during the preparation of the negative electrode sheet, and the other conditions are the same as those of Example 1.

[0074] Comparative Example 2

[0075] The difference between Comparative Example 2 and Example 1 is that: in Comparative Example 2, 0.5 wt % polyacrylic acid is added during the preparation of the negative electrode plate, and the other conditions are the same as those of Example 1.

[0076] Comparative Example 3

[0077] The difference between Comparative Example 3 and Example 1 is that: Comparative Example 3 does not perform compaction during the preparation of the negative electrode sheet, and the other conditions are the same as those of Example 1.

[0078] Embodiment 15

[0079] This embodiment 15 provides an electrical device, which includes the lithium-ion battery of embodiment 1.

[0080] Example 16

[0081] This embodiment 16 provides a method for predicting and regulating the membrane resistance of a lithium-ion battery. The method is: based on the average membrane resistance R of the constructed negative electrode sheet, β The relationship satisfied: 0.9≤R β / |(e (1-(a / (a+b)) -0.8×c) / 100|≤1.1, and according to the following relationship

[0082] 2×10 -3 ≤|(e (1-(a / (a+b)) -0.8×c) / 100|≤1.5×10 -2 According to the mathematical formula constructed above, the membrane resistance of the lithium-ion battery can be predicted and regulated by adjusting the mass percentage a of the second conductive agent in the negative electrode coating material, adjusting the mass percentage b of the second binder in the negative electrode coating material, and adjusting the compaction density c of the negative electrode sheet. The mathematical formula constructed according to the present invention can more accurately predict the membrane resistance R of the negative electrode sheet. β , so as to achieve the purpose of predicting and regulating the membrane resistance of lithium-ion batteries.

[0083] test:

[0084] (1) Compaction test method for negative electrode sheet:

[0085] ① First, the negative electrode sheet that has been rinsed with dimethyl carbonate and vacuum dried is cut into 6 square samples of standard size (2.0 cm × 2.0 cm);

[0086] ② Then, wipe off the active material on the front and back of three square samples, rinse and dry them with ethanol, weigh them and calculate the average mass M1, and use a screw micrometer to measure the average thickness L1 of the samples;

[0087] ③ Then, weigh the mass of the other three square samples and calculate the average mass M2. At the same time, measure the average thickness L2 of the samples and calculate the compaction density of the pole piece. The calculation formula is: Pole piece compaction density = , unit: g / cm 3 .

[0088] Negative electrode sheet membrane resistance test method: The membrane resistance of the negative electrode sheets in Examples 1 to 14 and Comparative Examples 1 to 3 was measured using the 46-probe method of the RM2610 resistance test system (45 probes are arranged in a square matrix, with 1 probe serving as a ground probe). The specific process is as follows:

[0089] ① First, the negative electrode sheet, which had been rinsed with dimethyl carbonate and vacuum dried at 60°C for 6 hours, was divided into 40 square grid samples of 1.0 cm × 1.0 cm to ensure that the sample surface was flat;

[0090] ② Next, place the sample on the test device and use the pressure gauge to adjust the probe to apply a pressure of 10 to 200 MPa. Maintain the pressure for 10 seconds to ensure good contact between the probe and the sample. The contact area is 0.01 cm². During the test, the 20 outer probes apply a constant current to make the current flow through the surface, interface and negative electrode current collector of the negative electrode. At the same time, the 25 probes in the middle measure the voltage change in real time. Since the surface, interface and negative electrode current collector of the negative electrode have significantly different resistances, the measured voltage will reflect these differences.

[0091] ③Finally, the membrane resistance R1 is calculated according to Ohm's law and the fitting analysis method. Then, the same method is used to randomly select another 9 square grid samples on the above negative electrode sheet to measure the membrane resistance. The measured resistance values ​​are recorded as R2, R3, R4, R5, R6, R7, R8, R9, R10, R11, R12, R13, R14, R15, R16, R17, R18, R19, R20, R21, R22, R23, R24, R25, R26, R27, R28, R29, R30, R31, R32, R33, R34, R35, R36, R37, R38, R39, R40, R41, R42, R43, R44, R45, R46, R47, R48, R49, R50, R51, R5 10 ;

[0092] Finally, by calculating the arithmetic mean of these values, the average film resistance R of the negative electrode sheet actually tested is obtained. β (R β =(R1+R2+R3+R4+R5+R6+R7+R8+R9+R10 ) / 10), in order to comprehensively evaluate the conductive properties and uniformity of the negative electrode sheet.

[0093] (3) Test method for negative electrode peeling force:

[0094] ① First, the negative electrode sheet that has been rinsed with dimethyl carbonate and vacuum dried is cut into long strips of standard size (2.0 cm × 10.0 cm);

[0095] ② Next, use double-sided tape to fix the long strip sample on a flat thin steel plate, make sure the tape is attached to the center of the steel plate, then peel off the protective layer of the double-sided tape, stick the negative electrode strip sample to be tested on the double-sided tape, and use a pressure roller to evenly roll the long strip sample to ensure good adhesion;

[0096] ③ Next, tear off the unpasted end, bend the natural end of the torn electrode upward, and clamp it in the upper fixture of the tensile testing machine for a 180° peeling test. Record the tensile force curve. When the tensile force changes by no more than 10%, select it as a stable peeling section. Finally, divide the average tensile force of this section by the width of the long sample electrode to calculate the peel strength of the negative electrode.

[0097] The membrane resistance R of the negative electrode sheets of Examples 1 to 14 and Comparative Examples 1 to 3 predicted by the mathematical formula of the present invention α , the average film resistance R of the negative electrode sheets of Examples 1 to 14 and Comparative Examples 1 to 3 actually measured by the above method β , and the peeling force results of the negative electrode sheets of Examples 1 to 14 and Comparative Examples 1 to 3 are shown in Table 1 below:

[0098]

[0099] Note: The calculation formula for "deviation degree" in Table 1 is: Deviation degree = |R α -R β | / R α .

[0100] From the results of Examples 1 to 6 in Table 1, it can be seen that the negative electrode sheet of Example 1 has the lowest film resistance value, at which the mass percentage of carbon nanotubes to polyacrylic acid is 1:1, and deviation from this ratio will lead to an increase in the film resistance of the negative electrode sheet. This is because polyacrylic acid is uniformly distributed on the surface of the negative active material in a linear manner, and its carboxyl functional group can form dipole interactions or hydrogen bonds with functional groups such as hydroxyl groups on the carbon nanotubes, so that the carbon nanotubes are more evenly dispersed in the three-dimensional cross-linked network structure of polyacrylic acid, thereby improving the conductivity of the negative electrode sheet. However, when the content of carbon nanotubes is too high and the content of polyacrylic acid is low, the binding force between the negative active materials is weakened, which will lead to a decrease in the tensile strength of the negative electrode sheet. This is due to the lack of sufficient functional groups to help the carbon nanotubes to be evenly dispersed on the surface of the active material, resulting in a blocked conductive path, which ultimately affects the overall conductive performance. On the contrary, if the content of carbon nanotubes is too low and the content of polyacrylic acid is high, the conductive agent will not be able to effectively conduct electrons, which will also cause a decrease in the conductivity of the negative electrode sheet.

[0101] From the results of Examples 7 to 12 in Table 1, it can be seen that with the increase in the degree of compaction, the film resistance of the negative electrode sheet is significantly reduced, and the tensile strength of the negative electrode sheet is also increased. This phenomenon is attributed to the fact that the higher degree of compaction makes the combination between the active material and the current collector foil tighter, thereby effectively reducing the impedance during the electron conduction process. At the same time, from the results of Examples 1 to 14 in Table 1, it can be seen that the film resistance R estimated by the mathematical model of the present invention is α Compared with the measured average film resistance R of the negative electrode β The deviation of the results is low (≤10%), which shows that the mathematical formula constructed by the present invention can accurately predict the membrane resistance of the negative electrode plate, and can provide an effective guidance scheme for the optimal design of the negative electrode plate, which is beneficial to optimize the design of the negative electrode plate, reduce the resistance, and thus improve the rate performance of the battery. Moreover, when the negative electrode plate is optimized according to the mathematical model of the present invention, the optimization process can be simplified, thereby effectively improving the efficiency of the battery design.

[0102] It can be seen from the results of Comparative Examples 1 to 3 in Table 1 that when no carbon nanotubes or polyacrylic acid are added, and no compaction treatment is performed, the membrane resistance of the negative electrode plate will increase significantly, and there is a large deviation from the membrane resistance value estimated by the mathematical model. This shows that the appropriate addition of the second conductive agent and the second binder in the present invention and the reasonable compaction process are crucial to optimizing electrode performance. Therefore, Example 1 has the optimal ratio of conductive agent and binder and the optimal compaction conditions, and therefore has the lowest negative electrode plate membrane resistance. Comparing Examples 1 to 12, it can be seen that under limited conditions, the negative electrode plate membrane resistance R of the above Examples 1 to 12 is β All of them are consistent with the theoretical film resistance R αPreferably, when the peel strength of the negative electrode sheet of the lithium-ion battery of the present application is 7.5-15.5 N / m, the lithium-ion battery has better electrochemical performance.

[0103] (3) Battery rate performance test method: Place the battery in a 25°C constant temperature box for 4 hours and test it according to the following steps:

[0104] 1. Charge to 4.2V at constant current and constant voltage at 0.1C, with a cut-off current of 0.01C, and let stand for 10 minutes. The capacity charged to 4.2V at constant current is counted as Q1.

[0105] 2. Discharge at a constant current of 0.1C until the battery is cut off at 2.5V, with a cut-off current of 0.01C, and leave it for 10 minutes;

[0106] 3. Charge to 4.2V at constant current and constant voltage at 1C, with a cut-off current of 0.01C, and let stand for 10 minutes. The capacity charged to 4.2V at constant current is counted as Q2.

[0107] 4. Discharge at a constant current of 0.1C until the battery is cut off at 2.5V, with a cut-off current of 0.01C, and leave it to stand for 10 minutes;

[0108] 5. Charge to 4.2V at constant current and constant voltage at 2C, with a cut-off current of 0.01C, and let stand for 10 minutes. The capacity charged to 4.2V at constant current is counted as Q3;

[0109] 6. Discharge at a constant current of 0.1C until the battery is cut off at 2.5V, with a cut-off current of 0.01C, and leave it for 10 minutes;

[0110] 7. Charge to 4.2V at constant current and constant voltage at 3C, with a cut-off current of 0.01C, and let stand for 10 minutes. The capacity charged to 4.2V at constant current is counted as Q4;

[0111] 8. Discharge at a constant current of 0.1C until the battery is cut off at 2.5V, with a cut-off current of 0.01C, and leave it for 10 minutes;

[0112] 9. Charge to 4.2V at constant current and constant voltage at 4C, with a cut-off current of 0.01C, and let stand for 10 minutes. The capacity charged to 4.2V at constant current is counted as Q5;

[0113] 10. Discharge at a constant current of 0.1C until the cutoff voltage reaches 2.5V, the cutoff current is 0.01C, and let stand for 10 minutes.

[0114] The calculation method of capacity retention rate is: Q X / Q1*100, X is 2, 3, 4, 5.

[0115] The capacity retention rates of the batteries of Examples 1 to 14 and Comparative Examples 1 to 3 in the constant current section under different rate conditions of 1C, 2C, 3C and 4C were statistically analyzed and compared, and the results are shown in Table 2 below:

[0116]

[0117] It can be seen from the results in Table 2 that the lower the measured membrane resistance of the negative electrode sheet, the higher the capacity retention rate during the 1C, 2C, 3C and 4C rate charge and discharge processes, and the better rate performance can be shown. This phenomenon can be attributed to several key advantages brought by low membrane resistance: First, lower membrane resistance means that the conduction efficiency of electrons in the negative electrode material is higher. This is because the reduction in resistance reduces the obstacles encountered during electron migration, thereby increasing the reaction rate between electrons and lithium ions. Under high-rate charge and discharge conditions, lithium ions need to be quickly embedded in and out of the negative electrode material. Low membrane resistance can ensure that this process proceeds smoothly, thereby effectively improving the capacity retention rate. Secondly, low membrane resistance helps to reduce polarization effects. During high-rate charge and discharge, the increase in polarization internal resistance and ohmic internal resistance will lead to capacity loss, especially during rapid charge and discharge. These internal resistance effects can be alleviated by reducing the membrane resistance, so that the concentration difference of lithium ions inside the electrode is kept within a small range, thereby reducing the capacity decay caused by concentration polarization. From Table 2, it can be seen that the discharge capacity retention rate of the lithium-ion battery of the present application under 1C charging is about 83.5-94.0%, the capacity retention rate under 2C charging is about 67.3-80.0%, the capacity retention rate under 3C charging is about 51.3-62.6%, and the capacity retention rate under 4C charging is about 41.6-54.8%. After calculation, the film resistance deviation degree (|R α -R β |) / R α The battery rate performance of less than or equal to 10% is obviously superior and more in line with actual product performance requirements.

[0118] In summary, the lithium-ion battery provided by the present invention can be used to calculate the negative electrode sheet resistance R by adjusting the mixing ratio of the conductive agent and the binder in the negative electrode coating material and the compaction of the negative electrode sheet in the lithium-ion battery. β , and the diaphragm resistance R β It has a strong correlation with the rate of lithium-ion batteries, which is conducive to optimizing the design of the negative electrode sheet, reducing the resistance, and thus improving the rate performance of the battery. According to the mathematical formula of the present invention, the film resistance R of the negative electrode sheet is β It is more convenient to perform optimization, which can improve the optimization efficiency and thus improve the efficiency of battery design.

[0119] The above are preferred embodiments of the present invention and are only used to explain the present invention, not to limit the present invention. Any obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A lithium ion battery, characterized in that: The lithium-ion battery includes a battery coil; The battery roll core is composed of a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet is composed of a positive electrode current collector and a positive electrode coating material coated on at least one surface thereof. The negative electrode sheet is composed of a negative electrode current collector and a negative electrode coating material coated on at least one surface thereof. The positive electrode coating material includes a positive electrode active material, a first conductive agent and a first binder. The negative electrode coating material includes a negative electrode active material, a second conductive agent and a second binder. The second conductive agent is selected from a material containing hydroxyl and carboxyl functional groups. The second binder is selected from a material containing carboxyl functional groups. The negative electrode active material is selected from at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon carbon, silicon oxygen and pre-lithium silicon oxygen. The silicon content in the negative electrode active material is 1.0 to 25.0 wt%; Among them, the average film resistance R of the negative electrode sheet β , unit is Ω·cm 2 , which satisfies the following relationship: 0.9≤R β / |(e (1-(a / (a+b)) -0.8×c) / 100|≤1.1; where: a represents the mass percentage of the second conductive agent in the negative electrode coating material; b represents the mass percentage of the second binder in the negative electrode coating material; c represents the compaction density of the negative electrode sheet g / cm 3 ; also meets the following conditions 2×10 -3 ≤|(e (1-(a / (a+b)) -0.8×c) / 100|≤1.5×10 -2 .

2. A lithium ion battery according to claim 1, characterized in that: The negative electrode coating material also includes a thickener.

3. A lithium ion battery according to claim 2, characterized in that: The thickener is sodium carboxymethyl cellulose, and its mass percentage in the negative electrode coating material is 0.5-1.5%.

4. A lithium ion battery according to claim 1, characterized in that: The second conductive agent is selected from carbon nanotubes or a combination of carbon nanotubes and carbon black; The second binder is selected from at least one of polyacrylic acid, polyacrylonitrile, and polystyrene-acrylic acid.

5. A lithium ion battery according to claim 1 or 4, characterized in that: The mass percentage a of the second conductive agent satisfies 0<a≤1.5%, and the mass percentage b of the second binder satisfies 0<b<3.0%; The mass percentage a of the second conductive agent and the mass percentage b of the second binder satisfy 1.0%≤a+b≤3.0%.

6. A lithium ion battery according to claim 1, characterized in that: The compaction density c of the negative electrode sheet meets 1.2 g / cm 3 ≤c≤1.8g / cm 3 .

7. A lithium ion battery according to claim 1, characterized in that: The capacity N / P ratio of the negative electrode plate to the positive electrode plate is (1.02-1.1):

1.

8. A lithium ion battery according to claim 1, characterized in that: The molecular formula of the positive electrode active material is Li a Ni x Co y Mn z M b O2; wherein, 0.9<a<1.2, 0.8≤x≤0.93, 0.1≤y<0.4, 0.05≤z<0.4, 0≤b≤0.1, and M represents at least one element selected from Zr, W, Ti, Al, Sr, La, B, and Nd.

9. A lithium ion battery according to claim 1, characterized in that: The first conductive agent is selected from conductive carbon black and / or carbon nanotubes, and the proportion of the first conductive agent in the positive electrode coating material is 1.0-3.0wt%; The first binder is polyvinylidene fluoride, and the proportion of the first binder in the positive electrode coating material is 1.0-3.0wt%.

10. A lithium ion battery according to claim 1, characterized in that: The electrolyte comprises a lithium salt, a solvent and an additive; The lithium salt is selected from any one or more combinations of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide; The solvent is selected from any one or more combinations of dimethyl carbonate, diethyl carbonate, ethylene carbonate, and ethyl methyl carbonate; The additive is selected from any one or more combinations of propylene carbonate, butylene carbonate, ethyl acetate, ethyl methyl carbonate, vinylene carbonate and fluoroethylene carbonate.

11. An electrical device, characterized in that: The electrical equipment comprises the lithium ion battery according to any one of claims 1 to 10.

12. A method for predicting and controlling the membrane resistance of a lithium-ion battery according to claim 1, characterized in that: The method is: according to the average film resistance R of the negative electrode sheet β Satisfied relationship: 0.9≤R β / |(e (1-(a / (a+b)) -0.8×c) / 100|≤1.1, and according to 2×10 -3 ≤|(e (1-(a / (a+b)) -0.8×c) / 100|≤1.5×10 -2 The relationship is used to predict and control the membrane resistance of the lithium-ion battery by adjusting the mass percentage a of the second conductive agent in the negative electrode coating material, the mass percentage b of the second binder in the negative electrode coating material, and the compaction density c of the negative electrode sheet.

Citation Information

Patent Citations

  • Lithium ion battery and preparation method thereof

    CN103779602A

  • Negative electrode paste of lithium ion battery and lithium ion battery

    CN106531963A